Application of STPA on Small Drone Operations: A Benchmarking Approach. (2017) - Chatzimichailidou, Maria Mikela; Karanikas, Nektarios; Plioutsias, Anastasios
Abstract: The remarkable and continuous growth of the unmanned aircraft market has brought new safety related challenges, as those are recorded in various accident and incident reports. Although drones with an operating weight higher than 20-25Kgs are technologically advanced and often subject to standards (e.g., technical reliability, airspace management, licensing, certification), the regulatory framework for (ultra) light drones focuses almost exclusively on the limitations that the operatorneeds to consider. Thus, the protection from accidents seems to rely mostly on the competency of the operator to fly a drone safely, and his/her observance of the rules published by the respective authorities. In addition, the hazards lying in the interaction between an operator and a small drone have not been systematically studied. In this paper, we present (1) the first results from a System-Theoretic Process Analysis (STPA) based approach to the identificationof hazards and safety requirements in small drone operations, and (2) an adaptation of the Risk Situation Awareness Provision Capability (RiskSOAP) methodology in order to quantify the differences amongst 4 drone models regarding the extent to which they fulfill the safety requirements identified through STPA. The results showedthat the drones studied satisfy the safety requirements at low and moderate levels and they present high dissimilarities between them regarding the extent to which they meet the same safety requirements. Future work will include: (a) comparison of a larger sample of small drones against the safety requirements, as well as pairwise, and (b) assessment of the degree to which various regulatory frameworks worldwide address the safety requirements generated with STPA and assigned to the authority level.